PsycEXTRA Dataset 2012
DOI: 10.1037/e502412013-166
|View full text |Cite
|
Sign up to set email alerts
|

Effective Rotations: Action Effects Determine the Interplay of Mental and Manual Rotations

Abstract: The last decades have seen a growing interest in the impact of action on perception and other concurrent cognitive processes. One particularly interesting example is that manual rotation actions facilitate mental rotations in the same direction. The present study extends this research in two fundamental ways. First, Experiment 1 demonstrates that not only manual rotations facilitate mental rotations but that mental rotations also facilitate subsequent manual rotations. Second, Experiments 2 and 3 targeted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…In line with this idea, studies have pointed out similarities between manual rotation and virtual rotation (Ruddle & Jones, 2001), thus emphasizing the pertinence of virtual environments for real-life applications (Waller, 2000). Consistent with research showing the effect of haptic experiences on mental simulation (White, 2012), transfer might depend on active manipulation in an egocentric referential through physical or virtual interactions (Janczyk, Pfister, Crognale, & Kunde, 2012), a lacking component of paper-and-pencil training. Therefore, the dynamic features of block videogames might be underlining their efficacy to train mental rotation, as suggested by recent research on the relation between higher cognition and the motor system.…”
mentioning
confidence: 64%
“…In line with this idea, studies have pointed out similarities between manual rotation and virtual rotation (Ruddle & Jones, 2001), thus emphasizing the pertinence of virtual environments for real-life applications (Waller, 2000). Consistent with research showing the effect of haptic experiences on mental simulation (White, 2012), transfer might depend on active manipulation in an egocentric referential through physical or virtual interactions (Janczyk, Pfister, Crognale, & Kunde, 2012), a lacking component of paper-and-pencil training. Therefore, the dynamic features of block videogames might be underlining their efficacy to train mental rotation, as suggested by recent research on the relation between higher cognition and the motor system.…”
mentioning
confidence: 64%
“…Those studies, and also the study of Wexler et al (1998) who demonstrated that compatible manual and mental rotation results in faster reaction times and fewer errors have triggered studies on the importance of motor processes in mental rotation and suggested a link between motor preparation and mental rotation. However, Janczyk et al (2012) demonstrated in a series of studies that the connection between manual rotation movements and mental rotation could instead be the anticipated sensory output of the manual rotation.…”
Section: The Processing Stages Of Mental Rotationmentioning
confidence: 99%
“…Another theoretical explanation of the assumed advantages of the MA versus MH format relates to ideomotor theory (Greenwald, 1970) and effects of response-effect compatibility (Janczyk, Pfister, Crognale, & Kunde, 2012;Janczyk, Yamaguchi, Proctor, & Pfister, 2015). According to this theory, "it is easier to produce actions that predictably produce consequences that are compatible rather than incompatible with the action itself" (Janczyk et al, 2012, p. 2).…”
Section: Attitude Indicator Formatmentioning
confidence: 99%